2022
DOI: 10.3389/fnut.2022.830283
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Dietary Recommendations Based on Lipid-Related Genetic Variants: A Systematic Review

Abstract: BackgroundObesity and dyslipidemias are risk factors for developing cardiovascular diseases, the leading causes of morbidity and mortality worldwide. The pathogenesis of these diseases involves environmental factors, such as nutrition, but other aspects like genetic polymorphisms confer susceptibility to developing obesity and dyslipidemias. In this sense, nutrigenetics is being used to study the influence of genetic variations on the circulating lipid responses promoted by certain nutrients or foods to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 85 publications
(104 reference statements)
1
13
0
Order By: Relevance
“…The study of the effect of genetic differences between individuals on their response to a specific nutrient or dietary pattern for a specific health outcome (Nutrigenetics), and the study of the effect of foods on gene expression (Nutrigenomics) have enabled the development of the field of personalized nutrition and precision healthcare in the last years (1). Personalized nutritional counseling based on a person's genetic background may improve the outcomes of a specific dietary intervention and provide a novel therapeutic strategy for better control of cardiovascular disease or its related risk factors, such as diabetes, obesity, or blood lipid levels (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the effect of genetic differences between individuals on their response to a specific nutrient or dietary pattern for a specific health outcome (Nutrigenetics), and the study of the effect of foods on gene expression (Nutrigenomics) have enabled the development of the field of personalized nutrition and precision healthcare in the last years (1). Personalized nutritional counseling based on a person's genetic background may improve the outcomes of a specific dietary intervention and provide a novel therapeutic strategy for better control of cardiovascular disease or its related risk factors, such as diabetes, obesity, or blood lipid levels (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the proinflammatory, procoagulant, and prooxidant environment that characterizes the physiological response to dietary intakes, particularly a high-fat meal (11,12). Specifically, the main mechanisms proposed for atherosclerosis induced by postprandial lipemia include: (1) endothelial dysfunction induced by increased plasma TG with decreased serum nitrite/nitrate levels and flow-mediated dilation, (2) an increase in reactive oxygen species mediated through mitochondrial dissociation and beta-oxidation, (3) increased expression of adhesion factors at the subendothelial level, (4) activation of complement component factor 3, and (5) upregulation of proinflammatory and pro-apoptotic genes in endothelial cells following fat intake (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study suggesting an interaction between SIDT2 and nutrients with HDL-c concentrations. However, current studies have also observed significant interactions between the genetic variants involved in HDL-c metabolism and nutritional factors on HDL-c levels [ 64 , 65 , 66 , 67 ]. Supporting our results, earlier studies have shown that a high-fat intake can increase the HDL-c concentrations through more substrate provided in the chylomicron-derived triglycerides and increased lipoprotein lipase (LPL) activity.…”
Section: Discussionmentioning
confidence: 99%
“…[8,75,76] In terms of precision nutrition interventions, we highly recommend further studying the proposed panel's interactions with responses to different dietary patterns, bioactive foods, meal timing, and specific food cultures. [77,78] Integrating genetic panels such as the one proposed in this review, rather than a single genetic variant, will help to improve precision nutrition interventions that are effectively used in the prevention and treatment of dyslipidemias.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%